(untitled) (Scientific journal of the Fergana State University, 2025)
The article examines the theoretical and methodological foundations of the study of gnoseological and theological views of the medieval Muslim East, the development trends of the philosophical views of Eastern scholars, the interrelation of gnoseological and theological teachings in the medieval Muslim East, and the role of gnoseological and theological views in ensuring the harmony of religious and secular knowledge. The philosophical issues of the study of theological and gnoseological views are also analyzed.